Polyhydroxybutyrate in Rhizobium and Bradyrhizobium: quantification and phbC gene expression - Paganelli, Fernanda Laroza [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP]; Carareto Alves, Lucia Maria [UNESP] (Springer, 2011)
Polyhydroxyalkanoates (PHAs) are hydroxyalkanoate polymers that are produced and accumulate by many kinds of bacteria. These polymers act as an energy store for bacteria. Polyhydroxybutyrate (PHB) is the most studied polymer in the PHA family. These polymers have awakened interest in the environmental and industrial research areas because they are biodegradable and have thermoplastic qualities, like polypropylene. In this work, we analyzed the PHB production in Bradyrhizobium sp., Rhizobium leguminosarum bv. phaseoli, and Rhizobium huautlense cultured with two different carbon sources. We did biochemical quantification of PHB production during the three phases of growth. Moreover, these samples were used for RNA extraction and phbC gene expression analysis via real-time PCR. The bacteria showed different manner of growth, PHB accumulation and phbC gene expression when different quantity and quality of carbon sources were used. These results showed that under different growth media conditions, the growth and metabolism of different species of bacteria were influenced. These differences reflect the increase or decrease in PHB accumulation.
Keywords: Biodegradable plastic; Polyhydroxyalcanoate; PHB production; Real-time PCR